The new Afghanistan : pawn of America? - Ram, Samay, 1939- (New Delhi : Manas Publications, 2004)
On the political conditions of Afghanistan post 2001; a study.
Includes bibliographical references (p. [207]) and index.
Keywords: Afghanistan -- Politics and government -- 2001-